Pengelolaan Akun Instagram @Surabayasparkling sebagai Media Komunikasi Pariwisata di Surabaya - Eunice Michelle Aurelia (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Tourism is identified with visits to interesting locations for vacation, recreation, and business purposes. Through tourism, visitors gain experiences involving various activities such as nature tourism, visiting historical sites, or enjoying entertainment. Instagram, as a social media platform, offers an efficient way to assist tourists in finding vacation spots. Instagram has features that support and simplify users’ tourism communication activities. This study analyzes the management of the Instagram account @surabayasparkling as a tourism communication medium for the city of Surabaya. The purpose of this research is to analyze the effectiveness of managing the @surabayasparkling Instagram account as a tourism communication tool in increasing the attractiveness and promotion of Surabaya’s tourism. The methodology includes content analysis, interviews with account managers and the Surabaya tourism office, surveys of tour guides who follow the account, and documentation. This study uses a descriptive qualitative approach, with data validity ensured through source triangulation. The results show that the @surabayasparkling Instagram account uses an interesting and informative content strategy, leveraging Instagram features such as photo posts, short videos, and stories to boost tourist interest in visiting Surabaya’s destinations. Instagram @surabayasparkling plays a significant role as an effective tourism communication medium in introducing and promoting Surabaya tourism. Proper content management and active interaction with followers are key factors in successfully increasing tourist attraction through social media.